Postoperative analgesic effectiveness and opioid sparing effect of ultrasound guided transverse abdominis plane block in total abdominal hysterectomy under general anesthesia - Malla, Mohammad Sadiq; Ashraf, Sameena; Taj, Arshi; Bhat, Rafiq Ahmed (Asian Journal of Medical Sciences, 2021)
Background: Ultrasound guided transvers abdominis plane (TAP) block is a recent modality of managing postoperative pain in lower abdominal surgeries. Aims and Objective: This study was carried out to evaluate postoperative analgesic effectiveness and opioid sparing effect of ultrasound guided transverse abdominis plane block in total abdominal hysterectomy. Materials and Methods: One hundred patients of age group 25 to 65 years enrolled for total abdominal hysterectomy under general anesthesia were studied in the postoperative period at Lal Ded Hospital, Government Medical College, Srinagar over a period of 18 months. Patients who received injection Ropivacaine by ultrasound guided TAP were kept in Group A and others who received only conventional analgesia were kept in Group B. Postoperative pain scores were assessed by VAS score at 1,2,3,4,5,6,12,18 and 24 hours. Time of first rescue analgesia, total opioid consumption and postoperative adverse events were also observed. Results: Postoperative VAS pain scores were significantly reduced at all time intervals in TAP bock group (Group A) when compared with conventional analgesia group (Group B). Mean time for first rescue analgesia was 377 min in Group A as compared to 169 minutes Group B and the difference was statistically significant (p<0.05). The mean opioid consumption in Group A was 104±4.38 mg and in Group B it was 324±26.15mg and the difference between the two was statistically significant (p<0.05). Postoperative adverse events were insignificant. Conclusion: Ultrasound guided TAP block provides effective postoperative analgesia and reduces opioid consumption in abdominal hysterectomy patients under general anesthesia.